Once upon a time. The complete fifth season [videorecording (DVD)] - Kitsis, Eddy; Horowitz, Adam, 1971- (Once upon a time., 2016)
When the Savior becomes the "Dark Swan," the lines between good and evil blur as Emma begins to relish the intoxicating taste of absolute power. Terrified she'll succumb, Emma and Hook visit Camelot to find the one person who may be able to aid them: Merlin. Unfortunately, King Arthur proves treacherous, and when he joins forces with a vengeful Zelena, Emma and Hook's hopes are shattered.